Upaya Preventif Diabetes Tipe 2 Melalui Edukasi Dan Skrining Gula Darah Puasa Pada Populasi Usia Produktif Di Kelurahan Grogol - Charissa, Olivia; Santoso, Alexander Halim; Gunaidi, Farell Christian; Putra, Feri Yanto; Felicia, Ivana (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2025)
Type 2 diabetes mellitus is a chronic metabolic disease that is increasingly found in the productive age population and can have a major impact on quality of life, especially due to risk complications such as heart disease, nerve disorders, retinopathy, and kidney damage. Early symptoms are often not recognized because they are considered minor complaints, such as fatigue or frequent urination, so many cases are not diagnosed in the early stages. The Community Service Program (PKM) implemented in Grogol Village aims to increase public awareness of the importance of early detection of diabetes through fasting blood sugar screening activities. This activity uses the Plan-Do-Check-Act (PDCA) approach, including checking glucose levels with the Point-of-Care Testing (POCT) tool, as well as counseling on risk factors and prevention of diabetes. Of the 71 participants involved, 19 people (26.76%) were identified as having diabetes, 8 people (11.27%) had prediabetes, and the rest had blood sugar levels within normal limits. These results indicate that early screening is very important to prevent diabetes progression and severe complications, and is a foundation for building public awareness to maintain metabolic health sustainably.